Psychological factors predicting emotional eating in university students: challenges for health and overall well-being - Edwin Gustavo Estrada-Araoz; Yasser Malaga-Yllpa; Jhemy Quispe-Aquise; Marilú Farfán-Latorre; Willian Gerardo Lavilla-Condori; Gilber Chura-Quispe; Elizabeth Orfelia Cruz-Laricano (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: in recent years, emotional eating has received increasing attention due to its impact on health and well-being. Various studies have shown that emotions can influence eating patterns, leading individuals to eat in response to affective states rather than physiological needs.